Veterans Treatment Courts: Do Status-Based Problem-Solving Courts Create an Improper Privileged Class of Criminal Defendants? - Allison E. Jones (Washington University Journal of Law & Policy, 2014)
Although veterans treatment courts themselves are a recent and developing innovation, veteran status and its intersection with criminal sentencing considerations has an increasingly substantial legal basis to draw on. Prior to the expansion of problem-solving courts to reach veterans, many state-level trial court judges already considered military service-related disorders as potential mitigating factors. More recently, several states have either passed or proposed legislation designating veteran or active military status as a statutory mitigating factor, and current federal sentencing guidelines follow a 2009 Supreme Court decision affirming the proper role of a defendant’s military history in the penalty phase. Given the weight of political and legal decisions supporting veteran status as a mitigating factor in criminal cases, veterans treatment courts might ultimately demonstrate the advantages of treatment as an alternative to incarceration. Part II of this Note examines the origins and current operations of veterans treatment courts, and outlines the policy arguments articulated in their favor and the legal concerns raised by critics. Part III discusses the treatment of veteran status in sentencing outside of the specialty court context, highlighting statutory and non-statutory state sentencing guidelines and the recent federal response to military service-related crime. Part IV provides an analysis of the propriety of the veterans court model in light of the current state of the law outlined in Part III, and proposes a path forward for veterans courts, taking both legal sources of support and public criticism into consideration.
Keywords: veterans treatment; veterans treatment court; military law